Women in STEM and Cultural Diversity: an international experience - Oliveira, Elaine H. T.; Gasparini, Isabela; Cristea, Alexandra I.; Black, Susan E. (Anais do Women in Information Technology (WIT); 2023: Anais do XVII Women in Information Technology, 2023)
‘Spread the message’ was the motto of our meetings. The most important was that the message that girls and women have a place in STEM courses and careers reached as many people as possible. So, with this project, funded by the British Council, we joined forces here in Brazil, with professors from the United Kingdom to, first, understand the differences in reality and, then, act in our communities. The project had seven phases and there was a lot of exchange of ideas, visits, lectures, workshops, interviews and much more. The results and impact are countless. Also with the interaction with the British Council and professors from other approved projects, we created the proposal of the Brazil Gender Equality Framework for Higher Education Institutions.